2015
DOI: 10.1016/j.oraloncology.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Carotid sparing intensity-modulated radiation therapy achieves comparable locoregional control to conventional radiotherapy in T1-2N0 laryngeal carcinoma

Abstract: Background Although intensity-modulated radiotherapy (IMRT) is a standard of care for many head and neck cancers, its use for carotid-sparing (CS) therapy in early-stage laryngeal carcinoma is controversial. Methods 330 consecutive patients with early-stage laryngeal carcinoma were treated from 1/1989 to 5/2011, including 282 CRT and 48 CS-IMRT patients. The median follow-up was 43 (CS-IMRT) and 66 (CRT) months. Results There was no difference in local failure rates comparing patients undergoing CS-IMRT wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 33 publications
0
56
0
Order By: Relevance
“…This definitive radiotherapy to the larynx results in a very high cure rate with very low morbidity. Newer treatment approaches utilize intensity modulated radiotherapy to treat the larynx while sparing the adjacent carotid arteries and achieves 88% local control rate at three years for T1–2N0 glottic SCC . This highly accurate localized treatment has been taken one step further by a Dutch group who limited radiotherapy to the single involved vocal cord and reported a two‐year local control rate of 100% .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This definitive radiotherapy to the larynx results in a very high cure rate with very low morbidity. Newer treatment approaches utilize intensity modulated radiotherapy to treat the larynx while sparing the adjacent carotid arteries and achieves 88% local control rate at three years for T1–2N0 glottic SCC . This highly accurate localized treatment has been taken one step further by a Dutch group who limited radiotherapy to the single involved vocal cord and reported a two‐year local control rate of 100% .…”
Section: Discussionmentioning
confidence: 99%
“…Newer treatment approaches utilize intensity modulated radiotherapy to treat the larynx while sparing the adjacent carotid arteries and achieves 88% local control rate at three years for T1-2N0 glottic SCC. 24 This highly accurate localized Data available for only 63 PCF (-) in active smoking; 64 PCF (-) in diabetic and COPD; 65 PCF (-) in preoperative albumin; 9 PCF (1) in cricopharyngeal myotomy; 58 PCF (-) and 9 PCF (1) in metronidazole and antiskin commensal antibiotic; 57 PCF (-) and 9 PCF (1) in PPI. PCF 5 pharyngocutaneous fistula; PTL 5 primary total laryngectomy; STL-LOR 5 Salvage total laryngectomy with radiation to the larynx only and no chemotherapy; STL-CRT 5salvage total laryngectomy with larynx and neck radiation PTL 5 primary total laryngectomy; STL-LOR 5 Salvage total laryngectomy with radiation to the larynx only and no chemotherapy; STL-CRT-Cis 5 salvage total laryngectomy with larynx and neck radiation plus cisplatin chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…It was proposed that an increased conformality with IMRT and organ motion may increase the risk of marginal failures (19). However, a previous clinical study of IMRT for early-stage glottic cancer reported that the local control outcomes were comparable with those with conventional RT (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, concurrent systemic chemotherapy has been administered to several patients with T2 tumors. Zumsteg et al (20) reported conventional RT (n=282) and IMRT (n=48) outcomes for patients with T1-2N0M0 glottic cancer. The IMRT target volume was the entire larynx.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in the specific context of LC patients, there is no study investigating the benefit of IMRT in comparison to conventional RT in terms of laryngeal functions. Some studies have, however, demonstrated a reduction of the average RT doses to the carotid arteries with IMRT in patients with early glottic cancer [8].…”
Section: Introductionmentioning
confidence: 99%